The synthesis of the novel Escherichia coli toxin—colibactin and its mechanisms of tumorigenesis of colorectal cancer - Zhang, Guojing; Sun, Daqing (Frontiers in Microbiology, 2024)
Escherichia coli is part of the normal flora of the human gut and performs vital functions; however, certain strains can cause disease in the host, impairing gut function and adversely affecting overall health. The pks gene cluster in the E. coli B2 serogroup encodes colibactin, a secondary metabolite and a potential gut toxin. However, the mechanism underlying colibactin production in E. coli is complex, and the function of the pks gene cluster is not fully understood. This review explores the complex mechanisms and processes by which the pks island in E. coli produces colibactin, clarifying the specific role played by the clbA-S genes within it. It also reveals the toxic effects of colibactin on the host cell’s DNA and elaborates the mechanisms that may be important in inducing the development of colorectal cancer, such as single-base substitution (SBS), small insertion/deletion (small indel) features (ID-pks), inter-chromosomal linkages (ICLs), and DNA double-strand breaks (DSBs). The elucidation of these mechanisms is of great significance for the further exploration and development of related drugs.